Benzophenanthridine alkaloids from the roots of Thalictrum microgynum Lecoy.ex Oliv. Issue 20 (18th October 2019) - Jiang, Jie; Ma, Haoran; Hu, Song; Cheng, Lu; Wang, Fuqian; Zhang, Geng
Abstract: A new benzophenanthridine alkaloid, 2, 3, 9-trimethoxy-7, 8-methylenedioxy-5-methylbenzo[c]-6(5H) phenanthridone (2 ) and a benzophenanthridine alkaloid first found from natural sources, 2, 3-dimethoxy-7, 8- methylenedioxy-5-methylbenzo[c]-6(5H)- phenanthridone (1 ) together with two known benzophenanthridine alkaloids, Dihydrosanguinarine (3 ) and Dihydrochelilutine (4 ) were isolated from the roots of Thalictrum microgynum Lecoy.ex Oliv. The structures of1 and2 were elucidated using various spectroscopic techniques including HRESIMS and 1 D and 2 D NMR. Antibacterial activity of these compounds were tested. Compound1, 3 and4 showed antibacterial activity against Staphylococcus aureus with MIC values of 50, 100, 25 μg/mL, respectively. Graphical Abstract: